THE INFLUENCE OF THE INTERACTIVE GROUP INVESTIGATION LEARNING MODEL ASSISTED BY INTERACTIVE LKPD ON IPAS LEARNING OUTCOMES, VIEWED FROM THE PERSPECTIVE OF LEARNING MOTIVATION OF FOURTH-GRADE STUDENTS AT UBUD DISTRICT ELEMENTARY SCHOOLS - Ni Putu Feni Sukmawati; I Ketut Suma; I Nyoman Jampel (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effect of the application of the Group Investigation learning model fostered by interactive LKPD on the learning outcomes of IPAS in terms of learning motivation of grade IV students at SD Gugus Ubud, Ubud District, Bali. The research used a quasi-experimental method. Non-Equivalent Design of Pretest-Posttest Control Groups. The population consists of 194 students and a research sample of 84 students. Data were collected using learning outcome tests and motivational questionnaires. Data were analyzed using Two-Way ANCOVA with one covariate. Research results: first, there is a significant difference in the learning outcomes of IPAS, and second, there is a significant interaction between learning models and learning motivation on IPAS learning outcomes. Thirdly, among students with high learning motivation, the learning outcomes of IPAS differed significantly between those taught using the Group Investigation model assisted by interactive LKPD and lastly among students with low learning motivation, there were also significant differences in IPAS learning outcomes. The conclusion is that the Group Investigation model assisted by interactive LKPD is effective in improving IPAS learning outcomes strengthened by high student learning motivation. The contribution of this research is to have an impact on improving learning and the use of digital learning media in elementary schools.